2019
DOI: 10.1016/j.landusepol.2018.12.009
|View full text |Cite
|
Sign up to set email alerts
|

The individual determinants of support for open space bond referendums

Abstract: The ubiquitous use of ballot referendums in the public finance of land conservation means that conservation policy is often made at the individual voter level. However, studies to date have relied on either aggregate vote outcomes or surveys of residents of small geographic areas facing high growth. In this article, we utilize an original national survey to investigate a series of questions that pertain to individual opinion on open space preservation with a special focus on respondents' perception of open spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…However, our findings can be compared somewhat to several articles that investigate voter support for growth control policies. Recent evidence by Prendergast, Pearson-Merkowitz, and Lang (2019) found that demographic variables that are determinants of open-space and land-use preferences in aggregate studies were not all statistically significant in a national public opinion survey of open-space preferences. They found that while racial identification and homeownership were related to increased support for open space, income and education were not.…”
Section: Resultsmentioning
confidence: 95%
See 2 more Smart Citations
“…However, our findings can be compared somewhat to several articles that investigate voter support for growth control policies. Recent evidence by Prendergast, Pearson-Merkowitz, and Lang (2019) found that demographic variables that are determinants of open-space and land-use preferences in aggregate studies were not all statistically significant in a national public opinion survey of open-space preferences. They found that while racial identification and homeownership were related to increased support for open space, income and education were not.…”
Section: Resultsmentioning
confidence: 95%
“…Instead, studies that exist are largely based on aggregate data from elections and case studies of local land-use decisions. In addition, the literature to date has failed to take into account whether or not the views attributed to individuals are a product of the ecological inference fallacy—where the actions that appear when using aggregate variables are not reliable for individuals (e.g., King, Tanner, and Rosen 2004; also see Prendergast, Pearson-Merkowitz, and Lang, 2019, specifically about ecological fallacy issues on views of land preservation).…”
Section: The Undeserving Poor Interjurisdictional Competition and Hmentioning
confidence: 99%
See 1 more Smart Citation
“…This result is consistent with Bento et al (2015) that find housing values are more responsive of amenity changes than rental rates. Despite typically strong results between partisanship and willingness to vote for land conservation (Altonji, Lang, and Puggioni 2016;Prendergast Pearson-Merkowitz, and Lang 2019), no such relationship exists between % Democrat and MWTP.…”
Section: Discussionmentioning
confidence: 99%
“…Deacon and Shapiro (1975) first lays out a theoretical foundation to allow individual demand for land preservation to be inferred from aggregate voting data. To better understand voter support for land preservation, subsequent studies have used this approach to investigate which factors contribute to the success of open space referenda (Kline 2006, Kotchen and Powers 2006, Nelson et al 2007, Banzhaf et al 2010, Prendergast et al 2019. One limitation of these empirical studies is that they focus only on the effects of observable socioeconomic variables, neglecting the effects of exogenous shocks like disaster events.…”
Section: Introductionmentioning
confidence: 99%